2007
DOI: 10.1088/0022-3727/40/8/012
|View full text |Cite
|
Sign up to set email alerts
|

Electron swarm parameters in water vapour

Abstract: Electron swarm parameters, such as the drift velocity and the ionization coefficient, in water vapor have been measured for relatively wide ranges in reduced electric fields (E/N) at room temperature. The drift velocity (W m ) was obtained based upon the arrival-time spectra of electrons by using a double-shutter drift tube for the E/N from 60 to 1000 Td, while the first and second ionization coefficients (α and γ) were determined by the steady-state Townsend (SST) method from 50 to 3000 Td. The comparison bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 16 publications
1
43
0
Order By: Relevance
“…The Townsend ionization coefficient α has been measured by Hasegawa et al, 28 but it can also be found as an eigenvalue of the Boltzmann collision operator as discussed in Ref. 29.…”
Section: High Fields (E/n 0 90 Td) Nonconservative Collisions Trmentioning
confidence: 96%
See 2 more Smart Citations
“…The Townsend ionization coefficient α has been measured by Hasegawa et al, 28 but it can also be found as an eigenvalue of the Boltzmann collision operator as discussed in Ref. 29.…”
Section: High Fields (E/n 0 90 Td) Nonconservative Collisions Trmentioning
confidence: 96%
“…In what follows we highlight the distinctive regions of E/n 0 , discuss the physical origins of the behaviour, and outline the computational challenges that are present in those regions. We should note that when nonconservative processes, such as attachment and ionization, become operative, the definition of transport coefficients (bulk and flux coef- 27 Hasegawa et al, 28,29 and Ruiz-Vargas et al 24 See text for a discussion of the differences between the bulk and flux drift velocities.…”
Section: The Distinctive Variation Of Transport Coefficients Withmentioning
confidence: 99%
See 1 more Smart Citation
“…The total error introduced by a series of the procedure was roughly estimated to be 4%. In addition to W r , we also deduced the mean-arrival-time drift velocity ͑W m ͒ from the arrival-time distribution of electrons at fixed positions in the manner same as Hasegawa et al 9 The drift velocity obtained in the present experiment is shown in Table II and Fig. 3 with the computational results.…”
Section: Resultsmentioning
confidence: 70%
“…The authors have measured the arrival-time distribution of electrons by a double-shutter electrode technique based on the ATS method, 8,9 demonstrating the ATS method experimentally in order to achieve a direct comparison of the parameters between the theoretical and experimental. In the course of the ATS measurement, we found that our apparatus enables us to measure also the spatial distribution of an isolated swarm under moderate field conditions ͑see next section͒ by moving the double-shutter electrode to collect incoming electrons along the drift direction ͑electric field direction͒ and to deduce directly a typical parameter, the drift velocity.…”
Section: Introductionmentioning
confidence: 99%